Epidemiology, clinical spectrum, and outcomes of severe malaria in Eastern Uganda: a prospective study - Cate Namayanja; George Paasi; Jimmy Patrick Alunyo; Denis Amorut; Charles Benard Okalebo; William Okiror; Paul Ongodia; Grace Abongo; Rita Muhindo; Yovani A. M. Lubaale; Peter Olupot-Olupot (Malaria Journal)
Abstract Background In sub-Saharan Africa, malaria remains a public health problem despite some reports of declining incidence in the period 2000–2018. Since 2019, there have been some reports of disease epidemics and resurgences in areas that had registered steep declines and unusual clinical presentations. This study aimed to describe the epidemiology, clinical spectrum, and outcomes of severe malaria in children among malaria-endemic Eastern Uganda, a region that has recently experienced disease epidemics. Methods This prospective study was conducted at Mbale Regional Referral Hospital, Uganda, from 08th May 2019 to August 15, 2023, as part of the Malaria Epidemiological, Pathophysiological and Intervention studies in Highly Endemic Eastern Uganda (EDCTP–TMA2016SF-1514-MEPIE Study). Children aged 60 days to 12 years who at admission tested positive for malaria and fulfilled the clinical World Health Organization criteria for surveillance of severe malaria were enrolled into the study following appropriate informed consent. Data were collected using a customized proforma on social demographic characteristics, clinical presentation, treatment, and outcomes. Laboratory analyses included complete blood counts, lactate, glucose, blood gases, electrolytes, metabolites, and coagulation markers. In addition, urinalysis using dipsticks was done. Data were analysed using STATA V15. The study had ethical and regulatory approval before data collection commenced. Results A total of 1,379 participants were recruited. The median age was 4 years (2 months–12 years). Most children 757/1379 (54.9%) were under 5 years, and 825/1379 (59.8%) were males. The common symptoms were fever 1368 (99.2%), poor appetite 1095 (79.5%), inability to sit upright 1051 (76.2%), vomiting 944 (68.4%) and yellow eyes 833 (60.4%). The common signs included prostration, haemoglobinuria and jaundice. Prolonged hospitalization was found in 284/1339 (21.2%) and was associated with impaired consciousness 116/166 (30.1%), P = 0.003; haemoglobinuria 514/705 (27.1%), P < 0.001 and jaundice 505/690 (26.8%) P < 0.001. The overall mortality was 40/1347 (3.0%). Children who had > 1 severity feature were at a higher risk of mortality. Conclusion In this prospective study of children with severe malaria in Eastern Uganda, the overall mortality was 3.0% and the more the disease clinical syndromes the higher the risk of death.